Iatrogenic Kaposi Sarcoma Precipitated by Anti-Tumor Necrosis Factor-Alpha (Anti-TNF-α) Therapy - Mariappan, Aathi Lakshmi (Cureus, 2021)
Kaposi sarcoma (KS) is a vascular neoplasm caused by human gammaherpesvirus 8 (HHV-8). Four subtypes of KS are described: classic (Mediterranean), epidemic (acquired immunodeficiency syndrome (AIDS)-associated), endemic (sub-Saharan Africa), and iatrogenic. Iatrogenic KS due to tumor necrosis factor-alpha (TNF-α) inhibitor therapy is particularly rare. A 66-year-old female with a history of seropositive rheumatoid arthritis (RA) presented with a skin lesion on her right second toe. Diagnosed with RA four years prior, she failed to respond to methotrexate, hydroxychloroquine, and etanercept. As a result, she was started on adalimumab. Approximately two months into therapy, she presented to the emergency room with a dark brown skin lesion on her right second toe. She underwent excisional biopsy of the mass, which demonstrated a tumor composed of spindle cells forming slit-like spaces with extravasated red blood cells. The tumor was positive for cluster of differentiation 31 (CD31), CD34, and HHV-8 immunostains and negative for smooth muscle antibody (SMA) and desmin immunostains, consistent with Kaposi sarcoma. Human immunodeficiency virus (HIV) serology was negative. The patient was diagnosed with iatrogenic KS. Adalimumab was discontinued. The patient was started on alitretinoin and underwent adjuvant radiation therapy to minimize recurrence. TNF-α is a pro-inflammatory cytokine that has been implicated in many inflammatory diseases and in cell apoptosis. While anti-TNF-α agents have improved outcomes in many immune-mediated diseases, higher rates of infections and malignancy have also been reported. The incidence of KS with anti-TNF-α therapy remains a rare entity. Therefore, it is extremely important for patients receiving biologic agents, including TNF-α inhibitors, to have a close follow-up and receive routine skin evaluation for malignancy. Clinicians should have a high index of suspicion for KS in such non-HIV patients started on immunosuppressive agents.